Pengembangan Instrumen Penilaian Higher Order Thinking Skills Pada Mata Pelajaran Pendidikan Agama Islam - Taufiqurrahman, Taufiqurrahman; Heryandi, M. Tubi; Junaidi, Junaidi (Jurnal Pendidikan Islam Indonesia, 2018)
Research on development of Higher Order Thinking Skill (HOTS) is aimed at: (1) to produce higher order thinking skills (HOTS) instrument of PAI class X SMK Ibrahimy 2 Sukorejo Situbondo and (2) to know the feasibility of higher order thinking SMK Ibrahimy 2 Sukorejo Situbondo seen from the results of student trials. This research was research of development of higher order thinking skills (assessment instrument using 4D model. Based on the results of the analysis on the book PAI package and making test questions created by teachers in SMK Ibrahimy 2 Sukorejo can’t measure the ability of higher order thinking (HOT). The ability of students was still relatively low known from the making of questions that still level 1.2 and 3, while the matter can be said higher order thinking (HOT) if it is in the realm of cognitive C4, C5, C6.